Evaluación de los niveles de ruido con y sin jardines verticales en un entorno controlado en el laboratorio de operaciones unitarias - España Bastidas, Kevin Joan (2025)
The main objective of the present research study focused on the evaluation of noise levels with and without vertical gardens in a controlled environment, with the objective of mitigating noise pollution. The research was carried out in the laboratory of Unit Operations of the National University of Chimborazo, a specialized space that provided the necessary conditions for an accurate evaluation. The methodology applied was based on a quantitative approach and an explanatory design, since we sought to understand the cause-effect relationship between the implementation of vertical gardens and noise reduction. For this purpose, a field research was chosen, in which acoustic measurements were taken in two scenarios: with and without vertical gardens. Specialized instruments, such as sound level meters and digital tachometers, were used to ensure the accuracy and reliability of the data collected. The results obtained showed that, in all cases, a noise reduction of approximately 16.5 dB and 16.2 dB was achieved when the vertical gardens were installed. In addition, the t-test yielded values that showed a significant difference between the scenarios with and without gardens. These results confirm the effectiveness of vertical gardens as a solution for noise abatement.